Aqueous Extract of Thymus Vulgaris-induced Prevention of Kidney Damage in Hypertensive Adult Male Albino Rat: Biochemical and Ultrastructural Study - Kensara, Osama A.; ElSawy, Naser A.; Header, Eslam A. (Pakistan Journal of Nutrition, 2012)
Different metabolic disorders including hypertension cause renal damage. The aim of this study was to study the effect of Thymus Vulgaris (TV) on kidneys of induced hypertensive rats through biochemical and ultrastructure examination. Thirty three adult male albino rats were divided into 3 groups 11 animals each (control, untreated and treated). The first (control) group was fed and followed up for 8 weeks by measuring the systolic BP. In the second group, hypertension was induced by ligation of left renal artery to have systolic BP >150 mmHg and was followed up till the end of study. The third group in which hypertension was induced were given TV as 100 mg/kg body weight daily. The surviving 11 rats per each group were weighed again and killed with an overdose of phenobarbital and blood was collected to measure the blood chemistry. Following laparotomy, right kidney was dissected and excised from each rat and divided into 2 parts: one part was immersed in 10% formal saline and prepared for light microscopic examination. The other parts was immersed into 2.5 % glutaraldehyde and prepared for electron microscopic examination using transmission microscopy in faculty of medicine Zagazig university Egypt. A Significant increased was noticed in creatinine and cholesterol in untreated in contrast to control and treated hypertensive rats. There was significant reduction of Blood Pressure (BP) on using TV in contrast to untreated group. In untreated hypertensive group some cortical fields showed scars surrounding obsolete shrinkage glomeruli with inflammatory infiltrates with reciprocal dilatation of their Bowman's capsules. Ultrastructure examination showed thick glomerular endothelium with obliterated endothelial fenestrations. In treated hypertensive group the rat kidneys showed preserved cortical appearance and normal trilaminar structure but with focal thickening. Induced hypertension in rats affected renal tissues with biochemical alterations which all can be improved and/or prevented by using Thymus vulgaris herbal extract.